Characterization of Eosinophilic Esophagitis From the European Pediatric Eosinophilic Esophagitis Registry (pEEr) of ESPGHAN. Issue 3 (9th August 2022) - Oliva, Salvatore; Dias, Jorge Amil; Rea, Francesca; Malamisura, Monica; Espinheira, Maria Céu; Papadopoulou, Alexandra; Koutri, Eleni; Rossetti, Danilo; Orel, Rok; Homan, Matjaž; Bauraind, Olivia; Auth, Marcus Karl-Heinz; et al.
Abstract : Objectives: Few pediatric data on phenotypic aspects of eosinophilic esophagitis (EoE) are available. The pEEr registry was developed to prospectively characterize children with EoE from Europe and Israel. Methods: pEEr is an ongoing prospective registry enrolling children with esophageal eosinophilia (≥15 eos/HPF). Anonymized data were collected from 19 pediatric centers. Data regarding demographics, clinical manifestations, endoscopy, histology, and therapies were collected. Results: A total of 582 subjects (61% male) were analyzed. The median age at diagnosis was 10.5 years [interquartile range (IQR): 5.7–17.7], whereas the age at symptom onset was 9.2 years (IQR: 4.3–16.4), resulting in a median diagnostic delay of 1.2 years (IQR: 0.7–2.3). The diagnostic delay was longer below age <6 years. Shorter diagnostic delays were associated with the presence of food allergy or a family history for EoE. Symptoms varied by age with dysphagia and food impaction more common in adolescents, while vomiting and failure to thrive more common in younger children ( P < 0.001). Among endoscopic findings, esophageal rings were more common in adolescents, whereas exudates were more frequent in younger children( P < 0.001). Patients who responded to proton pump inhibitors (PPIs) were more likely to be older, males, and less often presented severe endoscopic findings. Patients unresponsive to PPIs received topical steroids (40%), elimination diet (41%), or a combined therapy (19%). Conclusions: EoE findings vary according to age in pediatric EoE. Young children are commonly characterized by non-specific symptoms, atopic dermatitis, food allergy, and inflammatory endoscopic lesions. Adolescents usually have dysphagia or food impaction, fibrostenotic lesions, and a better PPI response.